TASK ANALYSIS ON MAINTENANCE WORKER (RAIL GRINDER) OF LIGHT RAIL TRANSIT (LRT) - Jacquelyne AB; Azlis-Sani J; Nor Azali A; Nur-Annuar M; Shahrul Azhar S; Mifzal-Nazhan M (Malaysian Journal of Public Health Medicine, 2020)
Rail maintenance routines are necessary to enable the all rail operations to achieve its aim in maintaining a safe and efficient operation. The maintenance tasks expose the workers to vibration and noise, as they handle specialized machineries and heavy self-propelled vehicles. Exposure of noise above the permissible exposure limit and over the daily allowable duration may cause noise-induce hearing loss (NIHL). Investigation on the type of task that has high noise level exposure on the maintenance workers was conducted to justify the needs to further detailed of this study. This paper will describe the task analysis on maintenance workers and to identify possible tasks with exposure to high level of noise. It scopes down to grinding crew of the maintenance department of light rail transit. Methods used were real-time sound measurement using a sound level meter, observation and interviews. Then, data were analysed to understand the situation of exposure of noise during rail maintenance. An ergonomic risk assessment was also conducted by adoption of the latest guideline on Ergonomic Risk Assessment (ERA) at Workplace Guidelines recommended by Department of Occupational Safety and Health (DOSH), Malaysia. A hierarchical task analysis (HTA) was generated on the task of the maintenance worker, focusing on rail grinding crew. The newly generated HTA had allowed better understanding about the nature of work and the task conducted by a rail grinder during the work shifts. Tasks involving high noise level was identified. Data recorded shows that the noise level for the blowing activity was relatively high and exceeded the permissible exposure limit of 90dBA. The exposure level was currently controlled by practicing the usage of hearing protection equipment (HPE) and by controlling exposure time in accordance to recommendations of the Factory and Machinery Act (FMA). Thus, it had confirmed that maintenance workers were exposed to high noise levels when performing their daily task. Further studies are needed to investigate the relationship between the duration of exposure and noise-induce hearing loss (NIHL) with consideration of the lifestyles of the maintenance workers.